MicroRNA-7 Targets the KLF4 Gene to Regulate the Proliferation and Differentiation of Chicken Primary Myoblasts - Zhang, Genxi; Chen, Fuxiang; Wu, Pengfei; Li, TingTing; He, Mingliang; Yin, Xuemei; Shi, Huiqiang; Duan, Yanjun; Zhang, Tao; Wang, Jinyu; Xie, Kaizhou; Dai, Guojun (Frontiers in Genetics, 2020)
The proliferation and differentiation of chicken primary myoblasts (CPMs) play an important role in the development of skeletal muscle. In our previous research, RNA-seq analysis showed that microRNA-7 (miR-7) was relatively highly expressed in the proliferation phase of CPMs, but its expression level decreased significantly after CPMS-induced differentiation. Meanwhile, the mechanism by which the miR-7 regulates the proliferation and differentiation of CPMs is still unknown. In this study, we found that the expression levels of miR-7 and the Krüppel-like factor 4 (KLF4) gene were negatively correlated during the embryonic phase, and in vitro induced differentiation. A dual-luciferase assay and a rescue experiment show that there is a target relationship between miR-7 and the KLF4 gene. Meanwhile, the results show that overexpression of miR-7 inhibited the proliferation and differentiation of CPMs, while inhibition of miR-7 had the opposite effects. Furthermore, overexpression of the KLF4 gene was found to significantly promote the proliferation and differentiation of CPMs. Conversely, inhibition of the KLF4 gene was able to significantly decrease the proliferation and differentiation of CPMs. Our results demonstrate, for the first time, that miR-7 inhibits the proliferation and differentiation of myoblasts by targeting the KLF4 gene in chicken primary myoblasts.